Cross platform method for ubiquitous computing and its application to mobile terminal. (2016) - Liang, Wei; Xiong, Yonghua; Wu, Min; She, Jinhua
Commercially available mobile devices with various kinds of hardware and software platforms have resulted in a huge amount of mobile applications. This provides a big challenge to design applications that are compatible with heterogeneous devices and operating systems (OSes). This paper presents a method of cross platform mobile transparent computing (CPMTC) for mobile devices. A mobile pre-boot firmware (MPBF) is designed to stream OS image data to the device through a network. Moreover, in application layer, we devise a method of designing applications based on HTML5, which ensures that applications are available for different OSes. We use the MPBF to load different OSes into the experimental tablet. After that, we use the CPMTC method to run and evaluate a knowledge collection e-learning (KCE) system for different OSes. Experiment results confirm that the CPMTC is effective in separating OSes both from hardware and application programs for mobile devices.